2021
DOI: 10.1007/s10072-021-05127-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-term comparative analysis of no evidence of disease activity (NEDA-3) status between multiple sclerosis patients treated with natalizumab and fingolimod for up to 4 years

Abstract: Background Comparative effectiveness of natalizumab and fingolimod over a follow-up longer than 2 years has been not addressed yet. Objectives To compare the effect on no evidence of disease activity (NEDA-3) in relapsing-remitting multiple sclerosis (RRMS) patients treated with natalizumab or fingolimod for at least 4 years. Methods We included RRMS patients switched from first-line agents to natalizumab or fingoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…Real-world cohorts of persons with RRMS from single centers, multicenters, and national and international registries have been well utilized to explore the comparative effectiveness of natalizumab with another highly effective DMT, fingolimod, across clinical, radiological, disability, and disease activity outcomes (Barbin et al, 2016;Baroncini et al, 2016;Boziki et al, 2021;Braune et al, 2013;Curti et al, 2019;Guerra et al, 2021;Kalincik et al, 2015;Koch-Henriksen et al, 2017;Prosperini et al, 2017). The majority of these studies have shown natalizumab to be superior to fingolimod with regard to ARR, proportion of PwMS relapsing at 1 and 2 years and over longer time periods, short-term disability improvement, and proportions of PwMS with gadolinium (Gd)-enhancing lesions or new T2 lesions at 1 and 2 years (Barbin et al, 2016;Baroncini et al, 2016;Boziki et al, 2021;Kalincik et al, 2015).…”
Section: Comparative Effectiveness Of Natalizumab Versus Other Dmtsmentioning
confidence: 99%
See 1 more Smart Citation
“…Real-world cohorts of persons with RRMS from single centers, multicenters, and national and international registries have been well utilized to explore the comparative effectiveness of natalizumab with another highly effective DMT, fingolimod, across clinical, radiological, disability, and disease activity outcomes (Barbin et al, 2016;Baroncini et al, 2016;Boziki et al, 2021;Braune et al, 2013;Curti et al, 2019;Guerra et al, 2021;Kalincik et al, 2015;Koch-Henriksen et al, 2017;Prosperini et al, 2017). The majority of these studies have shown natalizumab to be superior to fingolimod with regard to ARR, proportion of PwMS relapsing at 1 and 2 years and over longer time periods, short-term disability improvement, and proportions of PwMS with gadolinium (Gd)-enhancing lesions or new T2 lesions at 1 and 2 years (Barbin et al, 2016;Baroncini et al, 2016;Boziki et al, 2021;Kalincik et al, 2015).…”
Section: Comparative Effectiveness Of Natalizumab Versus Other Dmtsmentioning
confidence: 99%
“…The majority of these studies have shown natalizumab to be superior to fingolimod with regard to ARR, proportion of PwMS relapsing at 1 and 2 years and over longer time periods, short-term disability improvement, and proportions of PwMS with gadolinium (Gd)-enhancing lesions or new T2 lesions at 1 and 2 years (Barbin et al, 2016;Baroncini et al, 2016;Boziki et al, 2021;Kalincik et al, 2015). Several studies use the metric of "no evidence of disease activity (NEDA) encompassing the absence of three clinical/imaging markers (NEDA-3)" -i.e., absence of relapses, no new radiological activity, and no confirmed disability progression (Wong et al, 2018) have shown a significantly higher proportion of PwMS treated with natalizumab than fingolimod achieved NEDA-3 at 2 years, with one study extending this observation to 4 years (Baroncini et al, 2016;Curti et al, 2019;Guerra et al, 2021;Prosperini et al, 2017).…”
Section: Comparative Effectiveness Of Natalizumab Versus Other Dmtsmentioning
confidence: 99%
“…Unfortunately, a decrease in NEDA-3 rates is frequently seen, even with high-efficacy DMTs. 23 In another study evaluating the NEDA status of 306 patients during their 3-year follow-up, the reason why NEDA could not be sustained in 64% of cases was evaluated due to MRI activity and one of the most important results of this study is the importance of intermittent imaging checks even in clinically stable MS patients (huhn et al, 2019). While only the presence of attack, MRI activity only, or progression in EDSS may be seen in patients unable to achieve NEDA-3, the course can also be observed with impairment in two or three parameters.…”
Section: Discussionmentioning
confidence: 91%
“…A study evaluating NEDA‐3 status in the second and fourth years of fingolimod and natalizumab therapies reported higher NEDA‐3 rates at two years, with a significant decrease in the fourth year. Unfortunately, a decrease in NEDA‐3 rates is frequently seen, even with high‐efficacy DMTs 23 . In another study evaluating the NEDA status of 306 patients during their 3‐year follow‐up, the reason why NEDA could not be sustained in 64% of cases was evaluated due to MRI activity and one of the most important results of this study is the importance of intermittent imaging checks even in clinically stable MS patients (huhn et al, 2019).…”
Section: Discussionmentioning
confidence: 91%
“…The copyright holder for this preprint this version posted October 13, 2022. ; https://doi.org/10.1101/2022.10.12.22280969 doi: medRxiv preprint the consistent results of the analyses of relapse outcomes in these 2 treatment groups suggests natalizumab could be superior to fingolimod on relapse outcomes. This is supported by relapse outcomes from comparative studies of natalizumab and fingolimod in patients with pediatric-or adult-onset MS. 38,[47][48][49] It is highly likely that lower relapse rates would also be associated with lower brain and spinal cord lesion accumulation, with potential for differential long-term benefits. In particular, cognitive and productivity outcomes, and risk of secondary progressive MS are potentially reduced with maximal control of the early inflammatory phase of RRMS.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%